Additive manufacturing of titanium alloys : state of the art, challenges and opportunities - Dutta, Bhaskar; Froes, F. H. (Butterworth-Heinemann is an imprint of Elsevier, 2016)
Additive Manufacturing of Titanium Alloys: State of the Art, Challenges and Opportunities provides alternative methods to the conventional approach for the fabrication of the majority of titanium components produced via the cast and wrought technique, a process which involves a considerable amount of expensive machining. In contrast, the Additive Manufacturing (AM) approach allows very close to final part configuration to be directly fabricated minimizing machining cost, while achieving mechanical properties at least at cast and wrought levels. In addition, the book offers the benefit of significant savings through better material utilization for parts with high buy-to-fly ratios (ratio of initial stock mass to final part mass before and after manufacturing). As titanium additive manufacturing has attracted considerable attention from both academicians and technologists, and has already led to many applications in aerospace and terrestrial systems, as well as in the medical industry, this book explores the unique shape making capabilities and attractive mechanical properties which make titanium an ideal material for the additive manufacturing industry.